Cerebellar Functional Lateralization From the Perspective of Clinical Neuropsychology - Starowicz-Filip, Anna; Prochwicz, Katarzyna; Kłosowska, Joanna; Chrobak, Adrian Andrzej; Myszka, Aneta; Bętkowska-Korpała, Barbara; Kwinta, Borys (Frontiers in Psychology, 2021)
Objective: The cerebellar functional laterality, with its right hemisphere predominantly involved in verbal performance, and the left one engaged in visuospatial processes has strong empirical support. However, the clinical observation and single research results show that the damage to the right cerebellar hemisphere may cause extra-linguistic and more global cognitive decline. The aim of our research was to assess the pattern of cognitive functioning, depending on the cerebellar lesion side, with particular emphasis on the damage to the right cerebellar hemisphere. Method: The study sample consisted of 31 patients with focal cerebellar lesions and 31 controls, free of organic brain damage. The Addenbrooke’s Cognitive Examination ACE III and the Trail Making Test TMT were used to assess patients’ cognitive functioning. Results: Left-sided cerebellar lesion patients scored lower than controls in attention and visuospatial domain, but not in language, fluency and memory functions. Participants with right-sided cerebellar lesion demonstrated a general deficit of cognitive functioning, with impairments not only in language and verbal fluency subscales but also in all ACE III domains, including memory, attention and visuospatial functions. The TMT results proved that cerebellar damage is associated with executive functions impairment, regardless of the lesion side. Conclusions: The cognitive profiles of patients with cerebellum lesions differ with regard to the lesion side. Left-sided cerebellar lesions are associated with selective visuospatial and attention impairments, while the right-sided ones may result in a more global cognitive decline, which is likely secondary to language deficiencies, associated with this lateral cerebellar injury.